A clinical approach to non-neutropenic fever in children with cancer. (April 2021) - AlAzmi, Aeshah; Jastaniah, Wasil; AlDabbagh, Mona; Elimam, Naglla
Background: There are a limited number of studies that address non-neutropenic fever episodes in children with cancer, and no standard approach exists. Method: We opt to retrospectively analyze the efficacy of the current clinical approach for management of non-neutropenic fever episodes and the associated risk factors among children with cancer at the Princess Noorah Oncology Center from May 2016 through December 2017. Results: A total of 480 non-neutropenic fever episodes were identified in 131 children, of which 62 episodes were triaged as high-risk non-neutropenic fever and 418 as low-risk non-neutropenic fever. Of those 480 non-neutropenic fever, 361 episodes (75.2%) were associated with the presence of central venous catheters. The overall failure rate of ceftriaxone mono-therapy was observed in 75.6% (11.7% in high-risk non-neutropenic fever with a mean C-reactive protein level of 21.1 (±23.2) mmol/L and 63.9% in low-risk non-neutropenic fever with a mean C-reactive protein level of 17.6 (±53.9) mmol/L). The overall bacteremia rate was 14.4%. The type of organisms isolated was mainly high-risk organisms in 59 non-neutropenic fever episodes (85.5%), OR 1.78 (95% CI: 0.45–7.04) p = 0.41. Of note, all bacteremia were associated with the presence of central venous catheter (100%). Of all the examined risk factors of outpatient treatment failure in low-risk non-neutropenic fever, only prolonged fever of more than three days were significantly associated with bacteremia OR 8.107 [95% CI: 1.744–37.691], p = 0.008. Noteworthy is that almost 43% of non-neutropenic fever episodes were associated with respiratory symptoms. This study provides a baseline for future prospective research assessing the pattern of non-neutropenic fever by focusing on associated risk factors.